Have we lost touch with the Prophet Amos’s warning? Church leaders and blood money rituals among youths in Nigeria - Uroko, F.C. (Acta Theologica, 2023)
This article reviews the literature on how religious leaders in Nigeria have become complacent and conspire in the corrupt activities of members of their congregations. Church leaders, who are meant to be guardians of ethics and morality, have lost it and are now dining with and covering people of dubious character. Some of these young people who engage in money rituals give money to these pastors, who accept it without inquiry. These young people are revered in the church and receive special prayers and honours. Others, who aspire to the same honours, seek ways to generate quick cash. This study investigates the role of church leaders in the growing ritual activities among Nigerian youths. It concludes by admonishing church leaders to emulate the life of Jesus, who was not afraid to speak the truth to the people whom he was shepherding.